Observation of symmetry-forbidden rectification in an inversion-symmetric Weyl metal - Yusuff Adeyemi Salawu; Yoonseok Choun; Seung-Jong Yoo; Minoru Sasaki; Ki-Seok Kim; Heon-Jung Kim (Nature Communications)
Abstract Conventional metals cannot undergo rectification at low-field regions because the existence of Fermi energy prohibits nonlinear responses. Similarly, materials with inversion symmetry typically do not exhibit rectification as it necessitates the inversion symmetry breaking in the conventional mechanism. In this study, we report our observation of symmetry-forbidden rectification in metals, realized as a non-equilibrium steady state in an inversion-symmetric Weyl metallic phase of Bi1-x Sb x (x = 3–4%). Constructing a van der Pol nonlinear differential equation derived from axion electrodynamics, we find an analytic steady-state solution that exhibits a symmetry-breaking bifurcation responsible for the rectification. Our experimental and theoretical results show the symmetry-forbidden nonlinear response as the manifestation of the spontaneous dynamical inversion-symmetry breaking in Weyl metals before reaching chaos.